Analysis and Critical Assessment of "We and our Philosophical Heritages" by "Mohammad Abed Al-Jabre" - Muslim .taheri; Yahya bouzarynejad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This study focused on the book "We and our Philosophical Heritage" as well as the position and attitude of Mohammed Abed al-Jabri, to achieve a clear understanding oh his works.. It also pays attention to external analysis and the origin of the work and its author. Inasmuch as the fact that non-cognitive factors affect the formation of thought, they need to be taken into account to describe the status of related work among other works in the field of specialization as well as the history of its formation. Then we discussed the internal analysis and place of work, the main topics, philosophy and methodology, assumptions, theories, in effect, a way of reasoning and logic, theory works and achievements, as well as references and citations.The most important part of this article is the evaluation of the effects of Jabre. In the final reflections on the content of the work and evaluation of  the form, structure and methodology, it is appropriate to consider the  consequences of scientific experts in the further investigation.